2020
DOI: 10.3390/ijms21093259
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Function, and Regulation of the Essential Virulence Factor Capsular Polysaccharide of Vibrio vulnificus

Abstract: Vibrio vulnificus populates coastal waters around the world, where it exists freely or becomes concentrated in filter feeding mollusks. It also causes rapid and life-threatening sepsis and wound infections in humans. Of its many virulence factors, it is the V. vulnificus capsule, composed of capsular polysaccharide (CPS), that plays a critical role in evasion of the host innate immune system by conferring antiphagocytic ability and resistance to complement-mediated killing. CPS may also provoke a portion of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 57 publications
1
32
0
Order By: Relevance
“…The identified BamD that annotated as OMP actually faced the periplasm side of the outer membrane ( Han et al, 2016 ). Vibrio was known to express the capsule (K antigen) on the cell to adapt the environment and escape the phagocytosis ( Pettis and Mukerji, 2020 ). This may limit the availability of OMPs to trypsin digestion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The identified BamD that annotated as OMP actually faced the periplasm side of the outer membrane ( Han et al, 2016 ). Vibrio was known to express the capsule (K antigen) on the cell to adapt the environment and escape the phagocytosis ( Pettis and Mukerji, 2020 ). This may limit the availability of OMPs to trypsin digestion.…”
Section: Resultsmentioning
confidence: 99%
“…The mask of many OMPs by capsule may also limit its reaction with antibodies, which should be considered in immunodetection and vaccine development. The expression of capsule of Vibrio was regulated by temperature, divalent cation (Ca 2+ and Mn 2+ ), oxygen content, and host environment ( Pettis and Mukerji, 2020 ). Further study of the surface proteome of V. parahaemolyticus with minimal capsule expression will elucidate more stably expressed OMPs and the optimal enrich broth for the immunodetection of V. parahaemolyticus from various environmental samples.…”
Section: Discussionmentioning
confidence: 99%
“…Vibrio vulnificus is an opportunistic foodborne pathogen that can cause primary septicemia with a high mortality rate. Previous reports demonstrated that V. vulniificus has some important virulence factors, such as capsular polysaccharide synthesis enzyme (CPS; cpsABCDFHIJ ), cytolysin ( vvhA ), RTX toxin ( rtxABCD ), and vibriolysin ( vvp ) ( Lee et al, 2008 ; Song et al, 2016 ; Elgaml and Miyoshi, 2017 ; Pettis and Mukerji, 2020 ). The genome analysis revealed that FORC_016 has these virulence genes, suggesting it is a virulent pathogen that can cause a foodborne outbreak ( Supplementary Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, FORC_016 may be resistant to broad-spectrum antibiotics. Capsular polysaccharide synthesis (CPS) plays an important role in bacterial capsule synthesis for host protection, biofilm formation, and resistance to opsonization by complement and subsequent phagocytosis ( Lee et al, 2013 ; Pettis and Mukerji, 2020 ). The CPS gene cluster in the FORC_016 genome consists of two parts: CPS transport (FORC16_0182-0185) and capsular polysaccharide synthesis (CPS cluster I, FOR16_0186-0197; and CPS cluster II, FORC16_3287-3294) ( Supplementary Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…To survive and proliferate in blood, V. vulnificus requires to overcome the innate immune defenses, including complement-mediated phagocytosis. Recently, capsular polysaccharide and Flp (fimbrial low-molecular-weight protein) pili are reported to play critical roles in evasion of the host innate immune system by resistance to complementmediated killing (66,67). Although an earlier work showed that virulent isolates produced high titers of hemolysin, were resistant to inactivation by serum complement (68), further information is needed to uncover the mechanism of VVHmediated evasion of complement killing, which may help us to better understand the basis of the V. vulnificus infection process in human blood.…”
Section: The Role Of the Vvh In Disease And Pathogenesismentioning
confidence: 99%